Sedanje stanje razširjenosti robinije (Robinia pseudoacacia L.) v Sloveniji in napovedi za prihodnost - Kutnar, Lado (Acta silvae et ligni, 2013)
In this study, we analyse the growing stock of black locust (Robinia pseudoacacia L.) and its share in Slovenian forests. In addition, based on empirical model and climate change scenarios, we predict its distribution and share in the future. Black locust is the commonest non-native tree species in Slovenian forests. The current growing stock of black locust is near 0.6% of the total growing stock of our forests. This tree species has the highest share in forests of the Regional Unit of Murska Sobota and Regional Karst Area Unit (Sežana). Should the recent climate change scenarios, which all predict an increase in mean air temperature in the future, proved to be true, the share of the black locust' growing stock will increase gradually in the eastern, north-eastern and south-western parts of Slovenia. Higher share of this species can be expected also in the lowlands and hilly area of central Slovenia. According to the forecasts of the model, the black locust's growing stock could at least double in comparison with its present state by the end of the century. In such situation our forestry will be faced with even more difficulties associated with this invasive tree species. Through a more consistent implementation of the concepts of sustainability in forestry, the balance between this invasive alien species, which is less desirable in our forests, and its many benefits and interests of the forest owners needs to be found.
Keywords: tujerodne vrste; invazivne vrste; lesna zaloga; Robinia pseudoacacia; robinja; podnebne spremembe; napovedi; modeli; Slovenia; Slovenija